International Trade and Economic Misery in African Countries with Low Human Development - Nwogwugwu, Uchechukwu C.; Umeghalu, Collins C. (International Journal of Finance Research, 2021)
Puzzled by the demeaning level of poverty most African countries continue to grapple with despite their extensive participation in international trade, the study attempts to examine the encumbrances that tend to impede African countries from optimally reaping the developmental gains inherent in partaking in international trade, which seems to also worsen the economic misery the inhabitants endlessly contend with. The System Generalized Method of Moments (System-GMM) estimation technique was used in the study which involves 17 African countries and spans from 1995 - 2018. While misery index is used to measure economic misery, the impact of international trade on economic misery is captured by means of its effect via economic misery, economic growth rate, balance of payment, total export, manufacture export and exchange rate. The results of the study reveal that balance of payments, total export, manufacture export, per capita GDP growth rate, exchange rate and lagged form of economic misery all have positive effect on economic misery. While the effects of total export, manufacture export, per capita GDP growth rate, and exchange rate on economic misery are significant, those of balance of payments and lagged form of economic misery are insignificant. While the study recommends that international trade be engaged strategically such that it results in favourable balance of payments, it also encourages the discarding of obsolete trade policies such as outright bans on importation of certain commodities. Bilateral trade agreements are recommended over multilateral trade agreements, since they are more mutually beneficial and binding on the parties involved